Past the Point of Speeding Up: The Negative Effects of Workload Saturation on Efficiency and Patient Severity - Berry Jaeker, Jillian A.; Tucker, Anita L. (Management Science, 2017)
Service organizations face a trade-off between high utilization and responsiveness. High utilization can improve financial performance, but causes congestion, which increases throughput time. Employees may manage this trade-off by reducing processing times during periods of high workload, resulting in an inverted U-shaped relationship between utilization and throughput time. Using two years of inpatient data from 203 California hospitals, we find evidence that patient length of stay (LOS) increases as occupancy increases, until a tipping point, after which patients are discharged early to alleviate congestion. More interestingly, we find a second tipping point—at 93% occupancy—beyond which additional occupancy leads to a longer LOS. These results are indicative of a workload-related “saturation effect” where employees can no longer overcome high workload by speeding up. Our data suggest that the saturation effect is due to an increase in the workload requirements of the remaining patients. Collectively, we find that the underlying relationship between occupancy and LOS is N-shaped. Consequently, managers who seek cost efficiencies via a strategy of high utilization in tandem with speeding up may find that their strategy backfires because there is a point at which employees are no longer able to compensate for a high workload by working harder, and throughput time counterproductively increases. We perform a counterfactual analysis and find that an alternate strategy of employing flexible labor when faced with high occupancy levels might be a more productive approach, and could save the hospitals in our sample up to $138 million over 23 months. This paper was accepted by Serguei Netessine, operations management.